Advancements in sustainable architecture and energy efficiency - González-Lezcano, Roberto Alonso, 1971- (Practice, progress, and proficiency in sustainability (PPPS) book series., 2021)
"This book addresses the different perspectives of energy consumption and demand to ensure sustainable energy, increased energy efficiency, improved energy policies and reasonable energy costs"--